Toward a Molecular Classification of Colorectal Cancer: The Role of Telomere Length - Baichoo, Esha; Boardman, Lisa A. (Frontiers in Oncology, 2014)
Telomere biology is central to the maintenance of genomic stability and telomeric dysfunction is thought to be an early stage in carcinogenesis. Reports of telomere lengths and their ascribed colorectal cancer risks have been discordant, with both very short and very long telomeres implicated. Nevertheless, telomeres appear to play a very central role in cancer initiation. Telomere length changes also appear to impact disease burden, progression and overall survival. This review covers contemporary views on telomere biology and colorectal cancer risk, with a brief overview of analytical methods employed in telomere measurement. We conclude with arguments in favor of including telomere assessment in the molecular profiling of colorectal cancers.